PENGARUH KUALITAS BAHAN BAKU DAN PROSES PRODUKSI TERHADAP KUALITAS PRODUK PT. MENJANGAN SAKTI - Diovita Hilary; Imam Wibowo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to analyze the effect of the quality of raw materials on product quality at PT. Menjangan Sakti, the influence of the production process on product quality at PT. Menjangan Sakti and the quality of raw materials and production processes simultaneously on product quality at PT. Menjangan Sakti. The number of samples in this study were 88 respondents. The analysis technique uses simple regression analysis and multiple regression. The results showed that the quality of raw materials and the production process simultaneously had a significant effect on product quality, because the quality of raw materials was maintained in terms of room temperature according to the type of raw materials stored and the production process where workers worked according to applicable regulations. The quality of raw materials has a positive effect on product quality. This shows that the quality of raw materials that are maintained in terms of room temperature according to the type of raw material stored can improve product quality. The production process has a positive effect on product quality. This shows that the workforce working according to the applicable regulations can significantly improve product quality.